MOBILE-ASSISTED LANGUAGE LEARNING: UTILIZING A SMARTPHONE TO LEARN ENGLISH VOCABULARY - Muhimmatush Sholihah; Muhammad Edy Thoyib (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Mobile-assisted language learning is a language learning method that includes teaching and practising mobile phones. This study aimed to study students' vocabulary and mastery by using Mobile Assisted Language Learning (MALL). Research has been conducted in class VII A at MTs Hidayatush Shibyan Tuban to decide whether mobile-assisted language learning has been successful. A pre-experimental methodology was used by the researcher to analyze the data using the t-test statistical formula. The results of this study are 70,9091 as pre-test and 91,3636 as post-test results. Researchers have found that students who learn to use smartphone supported Language Learning (MALL) help and master vocabulary. It can be concluded that the use of mobile-assisted language learning has extended the vocabulary of students.